2014
DOI: 10.1108/lr-05-2013-0062
|View full text |Cite
|
Sign up to set email alerts
|

Perceived usefulness, perceived ease-of-use and faculty acceptance of electronic books

Abstract: Purpose – This paper aims to extend the use of the technology acceptance model (TAM) to faculty acceptance of e-books at Sultan Qaboos University (SQU) in the Sultanate of Oman. Electronic books (e-books) are becoming increasingly important in society in general and among academic faculty, concomitant with the growth of portable electronic devices that facilitate the reading of e-books. Design/methodology/approach – The effects of langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…This result is in line with previous studies findings. The SST services, especially the self-check-in kiosk and bag drop kiosk, helps passenger free from extra effort during the check-in and bag drop process, and it enhances their trip experience (Amin et al., 2014; Liu, 2014; Nasser Al-Suqri, 2014; Chen et al., 2014). To add, Kashik et al.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in line with previous studies findings. The SST services, especially the self-check-in kiosk and bag drop kiosk, helps passenger free from extra effort during the check-in and bag drop process, and it enhances their trip experience (Amin et al., 2014; Liu, 2014; Nasser Al-Suqri, 2014; Chen et al., 2014). To add, Kashik et al.…”
Section: Resultsmentioning
confidence: 99%
“…Perceived usefulness adalah tolak ukur untuk menilai penerimaan pada teknologi dan untuk mengukur kesuksesan atau keberhasilan teknologi tersebut (Al-Suqri, 2014;Alsabawy et al, 2016). Terdapat beberapa dimensi penting dari perceived usefulness, menurut Segars & Grover (2015) yang menyatakan bahwa dimensi perceived usefulness terdiri dari work more quckly, job performance, increase productivity, effectiveness, makes job easier, dan useful.…”
Section: Hasil Dan Pembahasanunclassified
“…Venkatesh et al (2003) identified a number of intervening or moderating variables (gender, age, experience and voluntariness of use) that can influence use and behavioural continued usage intention of technology. Al-Suqri (2014) found that younger male faculty tended to have higher levels of e-resources usage than females and older faculty in Oman. Similar findings were reported by studies conducted in Nigeria (Funmilayo, 2013) and Tanzania (Manda and Mukangara, 2008).…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 88%
“…There are many studies (e.g. Al-Suqri, 2014; Barhoumi, 2016; Park et al , 2009) in developing countries which have employed TAM to study faculty members’ intentions to use e-resources. However, despite their widespread use, TAM and UTAUT have been criticised for paying no attention to the fact that technology acceptance may fluctuate over time (Venkatesh et al , 2007).…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%